2019
DOI: 10.21608/ejh.2019.19917.1203
|View full text |Cite
|
Sign up to set email alerts
|

Carisoprodol (Somadril) induced histological and histochemical changes in renal cortex of pregnant rats and their fetuses

Abstract: Background: Carisoprodol is a generally prescribed skeletal muscle relaxant whose primary active metabolite is meprobamate, a substance with well-established abuse potential similar to that of benzodiazepines. A number of reports showed that carisoprodol has been abused for its anodyne and relaxant effects. Aim: The diversion and misuse of carisoprodol and its adverse health effects appeared to be dramatically increased over the last several years. This study aimed to detect the histological and histochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…In the present study, amyloid-beta protein increased in the fetal skeletal muscles in S1 and S2 sets compared to the control set.These results agree with those of Abdelhafez and AbdRabou (20) who found increased amyloid-beta protein in the liver tissue of the fetal rat maternally treated with carisoprodol.The same authors added that amyloids are insoluble fibrous protein and they result from polypeptides and nearly 18 unsuitably folded forms of protein that present normally in the body.These misfolded constructions alter their good configuration and they erroneously interact with each other or other cell components forming insoluble amyloid fibers.Also, the present results agree with the study of AbdRabou and Alotibi (34) who found an increase in amyloid-beta protein in the fetal ileum tissues of the pregnant rat treated with carisoprodol. The same authors stated that the abnormal accretion of amyloidbeta protein in the tissues may play an important function in numerous neurodegenerative syndrome and cause amyloidosis.…”
Section: Skinsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, amyloid-beta protein increased in the fetal skeletal muscles in S1 and S2 sets compared to the control set.These results agree with those of Abdelhafez and AbdRabou (20) who found increased amyloid-beta protein in the liver tissue of the fetal rat maternally treated with carisoprodol.The same authors added that amyloids are insoluble fibrous protein and they result from polypeptides and nearly 18 unsuitably folded forms of protein that present normally in the body.These misfolded constructions alter their good configuration and they erroneously interact with each other or other cell components forming insoluble amyloid fibers.Also, the present results agree with the study of AbdRabou and Alotibi (34) who found an increase in amyloid-beta protein in the fetal ileum tissues of the pregnant rat treated with carisoprodol. The same authors stated that the abnormal accretion of amyloidbeta protein in the tissues may play an important function in numerous neurodegenerative syndrome and cause amyloidosis.…”
Section: Skinsupporting
confidence: 93%
“…In this work highly increased collagen fibres was detected in the epidermal and dermal layers especially hair follicles, hemorrhage and dilated capillaries were also observed in the treated fetal groups S1 and S2 compared to the control fetal groups. This investigation agrees with those of Abdelhafez and AbdRabou (20) who treated rats with somadril and they noticed highly increased collagen fibres in the renal tissues of pregnant rats of group S1 and S2 especially in the brush borders and basement membranes of the convoluted tubules.…”
Section: Skinsupporting
confidence: 92%
See 2 more Smart Citations